Fused and unzipped carbon nanotubes, electrochemically treated, for selective determination of dopamine and serotonin - Bonetto, Maria Celina (2018)
Glassy carbon electrodes (GC) were modified with multiwalled carbon nanotubes (MWCNT/GC) and electrochemically treated first by applying an oxidation potential and then a reduction potential. The resulting electrodes were characterized via scanning electron microscopy, Raman spectroscopy, energy dispersive spectroscopy, and electrochemical techniques, particularly cyclic voltammetry using the redox probes Fe(CN)6 3− /4- and Ru(NH3)2+/3+ and electrochemical impedance spectroscopy using Fe(CN)6 3− /4-. These modified electrodes showed an electrochemical determination selective for dopamine (DA) and serotonin (5HT) in the presence of ascorbic acid (AA) and uric acid (UA), simultaneously measured, with a high reproducibility (an RSD of 1.7% for DA and 1.6% for 5HT) and a limit of detection (LOD) of 235 nmol L−1 for DA and 460 nmol L−1 for 5HT. The GC electrodes modified with oxidized MWCNT, subsequently reduced, showed higher selectivity towards the oxidation of DA and 5HT compared with GC bare electrodes or modified with MWCNT or oxidized MWCNT.